Protestantes e política no Brasil : o perfil da atuação protestante na Câmara dos Deputados na década de 90 - Evandro Marcelo Alves Fernandes (2004)
The objective of the work is the political activity of Protestant deputies in the Chamber of Deputies in three legislatures (49th, 50th and 51st) that took place during the 1990s. To this end, in addition to studying their performance as deputies (votes and committees), the electoral connection (the bases) was also considered, as well as the historical relations of the Protestant segment with other religious segments, such as Catholics, and with political power. The main objective of the research is to say whether or not the so-called evangelical caucus, so much publicized in the media, exists, but also to clarify how the political activity of this segment represented in parliament takes place. The work starts from understanding the historical relationship between Catholicism and political power, prefigured in the State, especially during the military regime, as well as in periods prior to this. In the same way, it was done in relation to Protestants in their relationship with the State, with Catholics and with other Christian denominations (Pentecostals). Next, the study presents some of the main theories about congressional functioning, especially in relation to the most studied Congress in the world, which is the North American one, but also about the Brazilian one. Finally, the study advances the identification of Protestant politicians in the legislatures under examination and their performance in key votes, as well as their work in committees, among other aspects that help to outline the profile of these politicians at the time. The work allowed us to infer some things. There is a religious cleavage represented and expressed in Congress, but Protestant deputies cannot be considered a group of legislators differentiated from the group, from their peers. The Brazilian Congress is dominated by parties, which act based on the unequal distribution of power established by the Internal Regulations. To relate and better act in line with their electoral connection, Protestant deputies have three options: form a party, capture a party or organize themselves as an interest group (a bench). The third option is the most plausible, but it was not possible to confirm in this study, what is certain is that Brazilian Protestant deputies at the time acted as a parliamentary front. However, there is nothing stopping them from “using” one of the first two options in the future. Keywords: religion and politics; Protestants; Chamber of Deputies; evangelical bench.